Authenticity of the Sign: Travels of a Lahu Song - Pine, Judith (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
This is a paper about a song which requires rather complex semiotic operations to be Lahu. The Wedding Oath song indexes, in different contexts, a desirable modern quality in a pre-modern society, a connection between an ethnic minority group and the modern state which implies obligations toward that ethnic group, and the positive quality of cosmopolitanism as a characteristic of a modern nation state. The nature of authenticity as a feature of these indexical relationships creates the possibility that one might extend Mendoza-Denton’s (2011) concept of “semiotic hitchhiker” to incorporate a non-material feature of a discursive performance.